Anisotropic growth of oxide nanocrystals: Insights into the rutile TiO2 phase - Ribeiro, Caue; Vila, Cristiane; Stroppa, Daniel B.; Mastelaro, Valmor R.; Bettini, Jefferson; Longo, Elson [UNESP]; Leite, Edson R. (Amer Chemical Soc, 2007)
In this work, we report the synthesis of titanium oxide nanocrystals, especially the rutile TiO2 phase with nanorod morphology, by a method based on peroxotitanium complex decomposition. The results indicate that the anisotropic morphology reported for rutile TiO2 nanocrystals is related to the oriented attachment process. Despite the predominance of rutile nanocrystals at longer treatment times, the nanocrystals were obtained also in the anatase type, according to the degradation time adopted. XANES results evidenced the absence of structural correlation between the peroxytitanium complex and phase evolution, and the coexistence of the two phases strongly suggests a correlation of the oriented attachment mechanism and the rutile phase stabilization.